An object–oriented approach to port activity simulation. (10th April 2015) - Kondratyev, Mikhail
This paper discusses a technique for modelling cargo port activity. It is designed for a comprehensive evaluation of port efficiency under a given input of cargo traffic. An object–oriented extension of the conventional block–based approach to process–oriented discrete–event simulation is proposed to specify a model structure. A port modelling framework is implemented using the proposed technique and AnyLogic 6 simulation software. The framework consists of the custom AnyLogic library backed by a Java–based package of classes and interfaces. The library contains blocks, representing a set of typical vehicle handling processes in a port. The framework provides tools that allow for the rapid development of a cargo port model. It not only provides non–modifiable standard solutions but also allows thorough detailing of certain elements of the port infrastructure, if necessary.